At-Tahlil As-Sharfi: Ma'na Al-Fi'l Ats-Tsulatsi Al-Mazid fi Qasidah "Min Ayyi 'Ahdin fi Al-Qura Tatadaffaq" li Ahmad Shawqi: Morphological Analysis: The Meaning of the Triliteral Augmented Verb in the Poem "Min Ayyi 'Ahdin fi Al-Qura Tatadaffaq" by Ahmad Shawqi - Rahmat, Rahmat Hidayat; Fahmi , Fahmi Sofyan; Emi , Emi Suhemi (An-Nahdah Al-'Arabiyah, 2025)
This study discusses "The Meanings of Prepositions in the Poem Ayyuha al-Muntaḥi Bi-Aswān Dāran by Ahmad Shawqi (A Grammatical Study)." The research aims to identify and analyze the types and meanings of prepositions found in the poem. The method used in this study is the descriptive-analytical method, while the applied theoretical framework is grammatical analysis. The results of the study reveal a total of sixty-two (62) prepositions in the poem, categorized as follows: seventeen (17) instances of the preposition "بِ" (bi), eleven (11) instances of "مِن" (min), fourteen (14) instances of "في" (fī), eight (8) instances of "ك" (ka), three (3) instances of "رُبَّ" (rubba), five (5) instances of "على" (‘alā), three (3) instances of "لِ" (li), and one (1) instance of "إلى" (ilā). Each preposition carries different semantic functions, including adhesion, circumstantial meanings, accompaniment, emphasis, instrumentality, causality, partitivity, elevation, transitivity, and comparison. These findings demonstrate the diverse syntactic roles and meanings of prepositions in Arabic poetry, particularly in Ahmad Shawqi’s literary works.   يتناول هذا البحث "معاني حروف الجر في قصيدة أيها المنتحي بأسوان دارا لأحمد شوقي (دراسة نحوية)." يهدف البحث إلى تحديد وتحليل أنواع ومعاني حروف الجر الواردة في القصيدة. اعتمدت الباحثة على المنهج الوصفي التحليلي، مع تطبيق الدراسة النحوية كإطار نظري. توصلت الدراسة إلى وجود اثنين وستين (62) حرف جر في القصيدة، موزعة على النحو التالي: سبعة عشر (17) من "الباء"، أحد عشر (11) من "من"، أربعة عشر (14) من "في"، ثمانية (8) من "الكاف"، ثلاثة (3) من "رب"، خمسة (5) من "على"، ثلاثة (3) من "اللام"، وواحد (1) من "إلى". وتحمل هذه الحروف معاني نحوية متنوعة، منها الإلصاق، الظرفية، المصاحبة، التأكيد، الاستعانة، السببية والتعليل، التبعيض، الاستعلاء، التعدية، والتشبيه. وتبرز هذه النتائج الأدوار النحوية والتنوع الدلالي لحروف الجر في الشعر العربي، ولا سيما في أعمال أحمد شوقي الأدبية. Penelitian ini membahas "Makna Huruf Jer dalam Puisi Ayyuha al-Muntaḥi Bi-Aswān Dāran Karya Ahmad Shawqi (Kajian Nahwu)." Tujuan penelitian ini adalah untuk mengidentifikasi dan menganalisis jenis serta makna huruf jer yang terdapat dalam puisi tersebut. Metode yang digunakan adalah metode deskriptif-analitis, dengan pendekatan teori kajian nahwu. Hasil penelitian menemukan total enam puluh dua (62) huruf jer dalam puisi ini, dengan rincian sebagai berikut: tujuh belas (17) kali huruf jer "بِ" (bi), sebelas (11) kali "مِن" (min), empat belas (14) kali "في" (fī), delapan (8) kali "ك" (ka), tiga (3) kali "رُبَّ" (rubba), lima (5) kali "على" (‘alā), tiga (3) kali "لِ" (li), dan satu (1) kali "إلى" (ilā). Setiap huruf jer memiliki fungsi semantik yang beragam, seperti iltishāq (melekat), zharfiyyah (keterangan tempat/waktu), mushāḥabah (kebersamaan), ta’kīd (penegasan), isti‘ānah (alat), sababiyyah wa ta‘līl (sebab dan alasan), tab‘īḍ (sebagian dari sesuatu), isti‘lāʻ (ketinggian), ta‘diyah (pengalihan makna kata kerja), dan tasybīh (penyerupaan). Temuan ini menunjukkan peran sintaksis dan variasi makna huruf jer dalam puisi Arab, khususnya dalam karya sastra Ahmad Shawqi.